Improving Students' Reading Comprehension Using Combination Of Picture And Reading Materials (An Action Research on the Second Grade Students of SMP Negeri 1 Plupuh Sragen Academic Year 2010 / 2011) - Priyatno, Joko (2012)
The problem of second grade students at SMPN 1 Plupuh Sragen was lack of reading comprehension. It is caused by the lack of reading English texts and less motivation of reading. The research is carried out to arouse the students' motivation to read, in this case, reading English texts. Hopefully, they can improve their reading comprehension. The data were collected through observation, interview, tests and documentation. The qualitative data were collected through the students' participation in reading class. The observation was on the students' ability to do the exercises, join the group discussion and doing the tests. The data were supported by the informal interview after the reading class has been finished. It was carried out to find out the students' problems during the use of pictures and reading materials in the reading class. The quantitative data were obtained through the result of exercises and the post-test. The findings show that the use of pictures and reading materials in reading class gave some positive aspects. The first effect is on the students' affective factors such as motivation and self confident. The second effect is the change of the students' attitude toward the teaching learning process. The third effect is on the active participation during the reading class. The last but not the least is the improvement on reading comprehension, especially the reading score. The research finding implies that the use of pictures and reading materials can be an alternative technique to promote the students' reading comprehension. Therefore, it is recommended that the English teachers apply it. It is also recommended that the institution socialize the findings since it is useful for English subject. The last is for the other researcher to develop the aspect of reading comprehension which has not been developed in the research.